ЕКСПЕРИМЕНТАЛЬНЕ ДОСЛІДЖЕННЯ ФОРМУВАННЯ В УЧНІВ 7-Х КЛАСІВ УМІНЬ САМОКОНТРОЛЮ (Педагогіка вищої та середньої школи, 2022)
Irina Seregina’s article “The forming of skills of self-control of students of the 7th grade ” deals with the problem of forming skills of self-control of the students of basic school during the studying process. Experimental research o f the development of self-control of the students of the 7th grade was made at the Russian Language lessons.